The effects of urbanization on global Plasmodium vivax malaria transmission. - Qi, Q; Guerra, C; Moyes, C; Elyazar, I; Gething, P; Hay, S; Tatem, A (BioMed Central, 2012)
BACKGROUND: Many recent studies have examined the impact of urbanization on Plasmodium falciparum malaria endemicity and found a general trend of reduced transmission in urban areas. However, none has examined the effect of urbanization on Plasmodium vivax malaria, which is the most widely distributed malaria species and can also cause severe clinical syndromes in humans. In this study, a set of 10,003 community-based P. vivax parasite rate (PvPR) surveys are used to explore the relationships between PvPR in urban and rural settings. METHODS: The PvPR surveys were overlaid onto a map of global urban extents to derive an urban/rural assignment. The differences in PvPR values between urban and rural areas were then examined. Groups of PvPR surveys inside individual city extents (urban) and surrounding areas (rural) were identified to examine the local variations in PvPR values. Finally, the relationships of PvPR between urban and rural areas within the ranges of 41 dominant Anopheles vectors were examined. RESULTS: Significantly higher PvPR values in rural areas were found globally. The relationship was consistent at continental scales when focusing on Africa and Asia only, but in the Americas, significantly lower values of PvPR in rural areas were found, though the numbers of surveys were small. Moreover, except for the countries in the Americas, the same trends were found at national scales in African and Asian countries, with significantly lower values of PvPR in urban areas. However, the patterns at city scales among 20 specific cities where sufficient data were available were less clear, with seven cities having significantly lower PvPR values in urban areas and two cities showing significantly lower PvPR in rural areas. The urban-rural PvPR differences within the ranges of the dominant Anopheles vectors were generally, in agreement with the regional patterns found. CONCLUSIONS: Except for the Americas, the patterns of significantly lower P. vivax transmission in urban areas have been found globally, regionally, nationally and by dominant vector species here, following trends observed previously for P. falciparum. To further understand these patterns, more epidemiological, entomological and parasitological analyses of the disease at smaller spatial scales are needed.